Editorial. Issue 1 (1st April 2023) - Johansson, Bengt; Lilleker, Darren; Veneti, Anastasia; Vigsø, Orla
This article sets out the scope for the Journal of Visual Political Communication, the growing body of research in this field and introduces some of the key debates which are discussed by the essays in this special relaunch edition. The brief discussion firstly introduces power and symbolism, and who is represented and empowered through visual political communication. Secondly, the role of visuals in diplomacy and international relations. Thirdly, how visuals give a sense of proximity and closeness, exploring the role of photojournalists. Fourthly, the use of visuals for strategic impression management by political actors and the notion of authenticity. Fifthly, the role that user-generated visuals play within political communication. And, sixthly, the debates around computer-assisted, automated and artificial intelligence as tools for the analysis of visuals. The article gives insights into some of the important strands of research, debates which the journal seeks to explore.